Developing digital news in public service media - Sehl, A; Cornia, A; Nielsen, RK (Reuters Institute for the Study of Journalism, 2017)
In this report, we analyse how public service media organisations across six European countries are developing new projects and products to deliver digital news. All the organisations we cover here face various external challenges, including discussions around the funding, remit, and role of public service media, pressure from private sector media competitors, the rise of platform companies, and continued changes in media use. Our focus here is specifically on how they respond to these challenges and changes, and on the internal factors that those involved in developing new forms of digital public service news see as influencing the process of product development. Based on examples from each organisation and 36 interviews with both senior editors and managers as well as people directly involved in each project or product, we identify four foundational factors that our interviewees suggest are necessary for the successful development of new forms of digital news in public service media organisations, and three additional factors that seem to facilitate it.